The effect of hybridization on significant characteristics of jute/glass and jute/carbon-reinforced composites. (September 2017) - Sezgin, Hande; Berkalp, Omer B
In this study, four plied jute, carbon, E-glass fabric-reinforced and their hybridized composites are manufactured. Nine composite laminates with different stacking sequences are manufactured by vacuum infusion technique. In order to understand the structure of the composites, fiber weight and fiber volume ratios in the laminate system are initially figured out. Furthermore, void fractions of samples are calculated by using theoretical and experimental densities of the composite samples to examine the impact of amount of fiber content on the void fraction. The effect of hybridizing jute fabric-reinforced polyester composite with E-glass fabric and carbon fabric and also the effect of stacking sequence of fabric layers on the mechanical properties (tensile strength, impact strength) of composite laminates are investigated. According to the outcomes of this investigation, it is realized that incorporating high impact resistant fibers to the outer layers of the composites leads to higher impact resistance, and placing high tensile strength fibers at the inner layers results in higher tensile strength at the hybrid composite laminates.